1983
DOI: 10.1099/00207713-33-4-816
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping of Bdellovibrios by Agglutination and Indirect Immunofluorescence

Abstract: A comparative serological study was undertaken to clarify the uncertain interrelationships among various bdellovibrios. A total of 17 predacious (hostdependent) strains and 12 nonpredacious strains were serotyped. Strains were grouped into serotypes on the basis of positive agglutination and strongly positive fluorescence cross-reactions. The results of division of the strains into serogroups by these two methods were identical. Bdellovihrio starrii strain A3.12 and Bdellovibrio stolpii strain UKi2 were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The serologic heterogeneity of the halophilic Bd is manifest by these findings. This is consistent with findings that there may exist several serologic groups of nonhalopililic Bd (4,10) and that one nonhalophilic species alone (B. bacteriovorus) may contain as many as nine distinct serogroups. Of special interest was the finding that all 10 aquarium antigen preparations of Bd cross-reacted with antisera produced against an aquarium isolate.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The serologic heterogeneity of the halophilic Bd is manifest by these findings. This is consistent with findings that there may exist several serologic groups of nonhalopililic Bd (4,10) and that one nonhalophilic species alone (B. bacteriovorus) may contain as many as nine distinct serogroups. Of special interest was the finding that all 10 aquarium antigen preparations of Bd cross-reacted with antisera produced against an aquarium isolate.…”
Section: Discussionsupporting
confidence: 91%
“…Immunological parameters alone, or in combination with other techniques, may be useful tools in the taxonomy of halophilic Bd. Nonhalophilic Bd have been separated into several serologically distinct subgroups which may share a common antigen (2,5,10). Little is known regarding the number of different halophilic subgroups of Bd.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of diversity among Bdellovibrio species has also been demonstrated using physiological and cultural characteristics such as fatty acid composition , antibiotic resistance patterns and enzymic activities (H. N. Williams, unpublished data). An analysis of serological properties (Schelling et al, 1977), phage typing and physiological properties of the organisms has revealed that all three recognized species (B. bacteriovorus 100 T , B. stolpii Uki2 T and B. starrii A3.12 T ) form distinct groups (Althauser et al, 1972 ;Hashimoto et al, 1970 ;Varon & Levisohn, 1972).…”
Section: Introductionmentioning
confidence: 99%